Sustainable Development in Cities: A Qualitative Approach to Evaluate Rating Systems - Arabi, Soheil; Golabchi, Mahmood; Darabpour, Mehrab (Civil Engineering Journal, 2018)
Sustainable development paradigm is one of the dominant paradigms of the century. In 1987, â€œOur Common Future,â€ the Brundtland Commission adopted the concept of â€œsustainable developmentâ€ to challenge the dominant paradigm of development as equivalent to economic growth. Using rating systems is like a plan in order to implement sustainable development. Moreover, Tehran as the capital of Iran and a megalopolis needs an appropriate rating system to be assessed in context of sustainable development. Be that as it may, Selection of a rating system pivots on the paradigm of the planner that how the planner describes the development and what are the planner's preferences; and also on the priorities of the city planned to be developed. This research has tried to evaluate rating systems to unveil their qualities to afford city planners an opportunity to use an appropriate approach of sustainable development. Authors of this research hold the opinion that if planners' preferences and priorities of a city can be in step with a rating system, the best result will occur. Furthermore, it was decided to do the evaluation in the context of ASTM E2432. In this research rating systems of ISCA, BREEAM, LEED-ND, CASBEE, Green star, DGNB were chosen to be evaluated. On the other hand, the obstacles of implementing sustainable development in Tehran were identified. Finally, LEED-ND was identified as the best rating system among above-mentioned ones. Since the research was exploratory research, a qualitative approach was selected to do the evaluation. Consequently, structured interviewing was applied as a fitting method and the technique of pile sorting was used to collect data in interviews as well.